The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s13762-015-0828-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of carbon/phosphorus ratio on polyphosphate- and glycogen-accumulating organisms in aerobic granular sludge

Abstract: A laboratory-scale granular sequencing batch reactor, fed with acetate, was operated at two different ratios of chemical oxygen demand to phosphorus-15:1 and 100:1. Smaller aerobic granules, but with better settleability, were obtained at the lower ratio. High ratio of phosphorus release to uptake of dissolved organic carbon (0.42 mol/mol) coincided with high percentage of polyphosphate-accumulating organisms (up to 70 % of all bacteria) and implied high metabolic activity of these bacteria. Polyphosphate-accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…These moderate PR efficiencies could have been caused by the low biodegradability of tannic acid, which has been previously assessed [ 14 , 16 ]. A previous study [ 30 ] reported that polyphosphate accumulating organisms (PAO) accounted for 70% of all bacteria from AGS when the ratio COD/P was 15:1, which was associated with a high phosphorus release/dissolved organic carbon uptake ratio (0.4). The opposite trend was observed when the COD/P ratio was 100:1, favoring the glycogen accumulating organisms (GAO), which compete with PAO for a carbon source.…”
Section: Resultsmentioning
confidence: 99%
“…These moderate PR efficiencies could have been caused by the low biodegradability of tannic acid, which has been previously assessed [ 14 , 16 ]. A previous study [ 30 ] reported that polyphosphate accumulating organisms (PAO) accounted for 70% of all bacteria from AGS when the ratio COD/P was 15:1, which was associated with a high phosphorus release/dissolved organic carbon uptake ratio (0.4). The opposite trend was observed when the COD/P ratio was 100:1, favoring the glycogen accumulating organisms (GAO), which compete with PAO for a carbon source.…”
Section: Resultsmentioning
confidence: 99%
“…Competibacter abundance increased by >40% with the increasing rbCOD/P ratios from 20 to 50, but abundance of DF2 did not seem to vary, indicating that Competibacter was likely the one that responded to the change in loading ratio. Muszyński and Miłobędzka (2015) also observed increase in Competibacter abundance from 4 to 20% when the rbCOD/P ratio was changed from 15:1 to 100:1 with aerobic granular sludge while abundance of Alphaproteobacterial Defluvicoccus cluster 1 ( DF1 ) remained constant at 2% (they did not detect DF2 type GAOs in the granular sludge). These results clearly showed that both relative abundance and community compositions of PAOs and GAOs shifted as the influent rbCOD/P ratio changed.…”
Section: Resultsmentioning
confidence: 84%
“…Furthermore, Competibacter plays an important role in AGS formations. It has been identified as a GAO and has been found in AGS (de Kreuk & van Loosdrecht 2004;Weissbrodt et al 2013;Muszynśki & Miłobedzka 2015).…”
Section: Granulationmentioning
confidence: 99%